Palatability of Norway spruce needles infected with Lophodermium piceae to larvae of two sawfly species - Michael M. Müller; Leena Hamberg; Martti Varama (Silva Fennica, 2023)
Unequivocal evidence on the antagonistic effects of endophytic fungi associated with woody plants against insect herbivores has been documented in only a few cases so far. Experimental evidence of the significance of needle endophytes to coniferous trees has remained scant because it is difficult to obtain trees with needles free of endophytes that could be used as comparable controls for trees infected with endophytes. Previously we reported a new methodology to get Norway spruce (Picea abies (L.) Karst.) saplings without needle endophytes and to inoculate them with a needle endophyte Lophodermium piceae (Fuckel) Höhn. Here we describe the first trial where spruce saplings with and without needle endophytes were provided as substrate for insect larvae. We transferred larvae of two sawfly species, Neodiprion sertifer Geoffroy and Gilpina pallida Klug, to the seedlings. Even though the main host of these sawfly species is not Norway spruce, but Scots pine (Pinus sylvestris L.), they are also known to occasionally feed on spruce. In this experiment the larvae did not develop to pupae with the provided spruce substrate but consumed measurable amounts of needles. No significant difference was found between the extent of needles consumed by either of the two sawfly species in inoculated and uninoculated saplings.